THE AGGREGATE BEHAVIOR OF RETAIL INVESTORS IN THE RUSSIAN STOCK MARKET - Ya. M. Mirkin; S. A. Khestanov; A. O. Andryushenko; A. D. Volkova (Финансы: теория и практика, 2017)
The actions of people, their hopes and expectations lie at the heart of the dynamics of financial markets. This fact is a strong rationale for the study of the behavioral characteristics of investors. The topicality of this research is ensured by the rarity of the resembling publications in Russian professional and scientific journals. This article attempts to determine “who is who” on the Russian stock market.The main source of the information is the database provided by «Investment Holding FINAM» (data for period 2007 to July 2009). It reveals a proportion of the age groups of men and women in the total number of clients of the company based on the following parameters: total turnover, total funds, the number of customers.It has been determined that the male involvement is several times higher than the female participation according to all three parameters . The women of age of 50-55 and men of age of 55-60 have been classified as a group of the most attractive clients for financial intermediaries as they make long-term investments with relatively large funds.Further research, including the additional characteristics of the clients and based on more detailed time intervals, will provide a useful basis for the creation of the unique financial products on the Russian stock market.